Ovicidal, oviposition deterrent and larvicidal response of Anopheles stephensi Liston, 1901 to Lobophora variegata Lamouroux, 1817 from Tuticorin coast, Gulf of Mannar, India - Veni, T.; Pushpanathan, T.; Mohanraj, J. (Journal of Experimental Sciences, 2016)
The objective of the present study was to investigate the mosquito ovicidal, oviposition deterrent and larvicidal efficacy of hexane, benzene, chloroform, ethyl acetate and methanol extracts of, Lobophora variegata against malarial vector Anopheles stephensi. Among the five extract tested, the methanol extract was notable, which attained the 100 percent mortality at the concentration of 200.0 ppm and the hatchability rate ranged from 71.3 to 36.3 percent. In laboratory oviposition deterrent test, the extract of L. variegata greatly reduced the number of eggs deposited by gravid An. stephensi. The maximum and significant diminished fecundity in An. stephensi was observed with methanol extract which caused 76.15Ââ€“97.69% effective deterrence. Larvicidal response of An. stephensi was more susceptible in methanol extract. The LC50 Âvalue of methanol extract was 61.63 ppm and the Chi-square value were significant at p<0.05 level. It is concluded, that the extract ofÂ L. variegata could be used in control of malarial vector An. stephensi.